Effectiveness of Cathelicidin Antimicrobial Peptide against Ictalurid Catfish Bacterial Pathogens. Issue 3 (13th June 2021) - Simora, Rhoda Mae C.; Wang, Wenwen; Coogan, Michael; El Husseini, Nour; Terhune, Jeffery S.; Dunham, Rex A.
Abstract: One of the major goals in aquaculture is to protect fish against infectious diseases as disease outbreaks could lead to economic losses if not controlled. Antimicrobial peptides (AMPs), a class of highly conserved peptides known to possess direct antimicrobial activities against invading pathogens, were evaluated for their ability to protect Channel Catfish Ictalurus punctatus and hybrid catfish (female Channel Catfish × male Blue Catfish I. furcatus ) against infection caused by the fish pathogen Aeromonas hydrophila ML09‐119. To identify effective peptides, the minimum inhibitory concentrations against bacterial pathogens Edwardsiella ictaluri S97‐773, Edwardsiella piscicida E22‐10, A. hydrophila ML09‐119, Aeromonas veronii 03X03876, and Flavobacterium columnare GL‐001 were determined in vitro. In general and overall, cathelicidins derived from alligator and sea snake exhibited more potent and rapid antimicrobial activities against the tested catfish pathogens as compared to cecropin and pleurocidin AMPs and ampicillin, the antibiotic control. When the peptides (2.5 µg of peptide/g of fish) were injected into fish and simultaneously challenged with A. hydrophila through immersion, increased survival rates in Channel Catfish and hybrid catfish were observed in both cathelicidin (alligator and sea snake) treatments as compared to other peptides and the infected control ( P < 0.001) with alligator cathelicidin being the overall best treatment. Bacterial numbers in the kidney and liver of Channel Catfish and hybrid catfish also decreased ( P < 0.05) for cathelicidin‐injected groups at 24 and 48 h after challenge infection. These results show the potential of cathelicidin to protect catfish against bacterial infections and suggest that an approach overexpressing the peptide in transgenic fish, which is the long‐term goal of this research program, may provide a method of decreasing bacterial disease problems in catfish as delivering the peptides via individual injection or feeding would not be economically feasible.